Implementasi Pendidikan Kewirausahaan dalam Menumbuhkan Keterampilan pada Peserta Didik Madrasah Ibtidaiyah - Jimmi Kurniawan; Kun Nurachadijat (Departement of Mathematics Education, 2023)
Changes in the era of the industrial revolution 4.0 require adjustments and active efforts from educational institutions and the government to ensure that students are ready to face challenges and opportunities in the future. Critical, creative and innovative thinking skills, as well as positive character development, are very important in this era. Therefore, entrepreneurship education can be one of the efforts to help students develop the skills and character needed in the current industrial revolution era. Implementation of Entrepreneurship Education aims to develop skills, attitudes, souls and the ability to create something of value to oneself and others. Being creative, innovative, independent, leadership, good at managing money, and having an unyielding spirit are some of the entrepreneurial attitudes that need to be instilled in children from an early age. This needs to be instilled early on considering that the various economic challenges faced by Indonesia are getting bigger. These entrepreneurial values become important points in the formation of life skills in children. Besides through education in the family, entrepreneurship education can be implemented in an integrated manner with learning activities in schools. Madrasah Ibtidaiyah students can be trained to develop entrepreneurial attitudes, souls and abilities through various creative activities that can be integrated with the applicable curriculum. Various strategies and methods can be used by teachers to cultivate good values from the character of a successful entrepreneur. Entrepreneurship education taught since MI is expected to be able to reduce consumptive patterns in children by training them to create something of value and bringing the next generation to create jobs in the future. So in this case, teachers and parents have an important role to play in developing children's life skills and fostering interest and potential in children through entrepreneurship.